2014
DOI: 10.4067/s0717-97072014000100027
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Virgin Heterophasic Pp Copolymer Content on Moisture Absorption, Thermal and Mechanical Properties of Recycled Polyethylene Wood Flour Composites

Abstract: The effect of virgin heterophasic PP copolymer (vPP) content on moisture absorption, as well as on thermal and mechanical properties of recycled polyethylene/ wood flour composites was investigated. The polymer matrix of recycled post-consumed plastic waste (rPE) was composed of a matrix of LDPE and a part of PP. Wood flour of Pinus radiata was used as filler at a constant loading of 45 wt.%. rPE/vPP blends and their composites were manufactured by melt blending, and then by injection molding. The morphology o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The effect of wood flour of Pinus radiata as fillers at a constant loading of 45 wt.% of recycled post-consumed plastic waste reported to be influenced by virgin PP [43]. In the report, the addition of virgin PP improved tensile and flexural moduli and flexural strength of wood plastic/LDPE composites (WPC).…”
Section: Modifications and Properties Of Recycling Of Virgin And Wastmentioning
confidence: 98%
See 1 more Smart Citation
“…The effect of wood flour of Pinus radiata as fillers at a constant loading of 45 wt.% of recycled post-consumed plastic waste reported to be influenced by virgin PP [43]. In the report, the addition of virgin PP improved tensile and flexural moduli and flexural strength of wood plastic/LDPE composites (WPC).…”
Section: Modifications and Properties Of Recycling Of Virgin And Wastmentioning
confidence: 98%
“…The improvement in rheological morphology does not indicate an improvement in compatibility as well as mechanical properties [71]. Modification of recycled HDPE with treated natural fiber using NaOH, SLS, acetic anhydride, CaCO 3 filler, and zeolites as well as synthetic fibers is characterized with improvement in polymer dispersion, even distribution of fibers, interfacial adhesion, fiber tearing, micro-crack formation, modifier content and size, nature of the modifier, and reduction in void formation [20,43,[72][73][74][75]. This indicated the enhanced compatibility which corroborates the improvement in physical, mechanical, and thermal properties of the modified recycled thermoplastics and dictates its applications.…”
Section: Scanning Electron Microscopymentioning
confidence: 99%
“…Many studies investigated the potential of the polyolefin recycled matrix components for WPC [10,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. Chtourou et al [21] showed that municipal waste plastics composed of 95% PE and 5% PP and pulp fibers produced WPC with average tensile properties compared to virgin polyolefin.…”
Section: Introductionmentioning
confidence: 99%
“…Catto et al [31] showed that recycled polyolefin is a viable alternative due to its comparable physical and mechanical properties to virgin polyolefin. Adding virgin PP to recycled HDPE improves WPC properties [32]. De Oliveira Santos et al [33] showed that using recycled PET below the melting temperature could enhance the composites processing and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%